Millionaire legacy : 8 millionaire success strategies for achieving financial and emotional wealth - Curran, Thomas P. (Morgan James Publishing : Made available through hoopla, 2016)
"Millionaire Legacy" features eight success strategies self-made millionaires use to acquire an abundance of financial and emotional wealth. Each strategy is presented in an easy-to-follow manner that can be implemented by anyone. Featured Millionaires: Brendon Burchard, Author of "Millionaire Messenger" and founder of Experts Academy Sean D. Tucker, Highly respected aerobatic pilot and chairman of EAA Young Eagles Program Mark Victor Hansen, Co-author of "Chicken Soup for the Soul" Mike Filsaime, Internet marketing expert and consultant Bob Proctor, Featured in "The Secret" and author of "You Were Born Rich" Russell Brunson, Internet marketing trainer James Malinchak, Motivational speaker who appeared on ABC's Secret Millionaire television show Steve Harrison, Host of National Publicity Summit and publisher of Radio-TV Interview Report (RTIR) Three other remarkable individuals are featured for their perseverance to overcome adversities: Captain Chesley B. "Sully" Sullenberger, Captain of US Airways Flight 1549 who landed the plane on the Hudson River after it lost thrust following a bird strike Karolyn Grimes, Actress who starred with Jimmy Stewart in the classic movie "It's a Wonderful Life" Captain Julie Clark, Aerobatic pilot and retired Northwest Airlines captain Bonus Section: A twenty-five question "Millionaire Legacy Mindset Assessment" lets you discover how closely your mindset compares to a millionaire's. You are given a scoring chart, assessment report, and evaluation of results, which outline the steps you must take to attain the mindset of highly successful millionaires. Bonus Section: "The Road to a Million Dollars: 10 Areas for Wealth Creation" is included and details ten income opportunities that can generate substantial revenue.